2016
DOI: 10.4103/0971-9784.173041
|View full text |Cite
|
Sign up to set email alerts
|

Perceval S aortic valve implantation in an achondroplastic Dwarf

Abstract: Despite cardiovascular disease in patients with dwarfism is not rare; there is a lack of reports referring to cardiac interventions in such patients. Dwarfism may be due to achondroplasia or hormonal growth disorders. We present a 58-year-old woman with episodes of dyspnea for several months. She underwent on transthoracic echocardiography, and she diagnosed with severe aortic valve stenosis. She referred to our department for surgical treatment of this finding. In accordance of her anthropometric characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 4 publications
1
12
0
Order By: Relevance
“…Preoperative EOA was 0.5 cm 2 , and after decalcification, the aortic annulus was estimated to be 11 mm. 62 A small Perceval valve was implanted successfully, and postoperative course was uneventful. 62 Dedeilias et al 63 performed a prospective, randomized study comparing outcomes between SAVR with the Perceval (n = 25) and the Sorin Soprano stented valve (n = 25) in patients with an aortic annulus of less than 30 mm.…”
Section: Special Use and Off-label Experience Small Aortic Roots And mentioning
confidence: 97%
See 1 more Smart Citation
“…Preoperative EOA was 0.5 cm 2 , and after decalcification, the aortic annulus was estimated to be 11 mm. 62 A small Perceval valve was implanted successfully, and postoperative course was uneventful. 62 Dedeilias et al 63 performed a prospective, randomized study comparing outcomes between SAVR with the Perceval (n = 25) and the Sorin Soprano stented valve (n = 25) in patients with an aortic annulus of less than 30 mm.…”
Section: Special Use and Off-label Experience Small Aortic Roots And mentioning
confidence: 97%
“…No significant differences were found in mortality or complication rates as well as peak pressure and IEOA between the groups. 61 Baikoussis et al 62 reported SAVR with the Perceval in an achondroplastic dwarf. Preoperative EOA was 0.5 cm 2 , and after decalcification, the aortic annulus was estimated to be 11 mm.…”
Section: Special Use and Off-label Experience Small Aortic Roots And mentioning
confidence: 99%
“…Scafuri et al used a pediatric cannula for aortic valve replacement with root enlargement in a 56-year-old woman with achondroplasia; however, they encountered no problem during CPB [ 6 ]. Other studies have reported using adult cannulas for the repair of type A aortic dissection [ 7 ], aortic valve replacement [ 8 ], and pulmonary endarterectomy [ 9 ]. Despite no consensus on this matter, an adult cannulation can often be performed successfully and should be considered given that these studies reportedly mentioned increasing their CPB flow to maintain adequate tissue perfusion.…”
Section: Discussionmentioning
confidence: 99%
“…This valve is absolutely indicated in “difficult” cases like this, above described or other cases described in the literature. [ 7 ] The main indications of the Perceval S valve implantation are old patients with comorbidities, patients with porcelain aorta, and patients with small aortic root avoiding in this way the aortic root enlargement. [ 8 ] The points of this paper are the ideal option of the use of the sutureless Perceval S aortic valve in porcelain aorta and then, the importance of the preoperative CT scan of the chest.…”
Section: Discussionmentioning
confidence: 99%